The Role Of Islamic Character Education In Preventing The Formation Of Motorcycle Gangs Among Students At Bina Taruna 1 Vocational School Medan - Misnan; Leni Masnidar Nasution; Hanafiah, Muhammad Ali; Yuni Sari Br Surbakti; Widya Astuti (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
Abstract: The formation of motorcycle gangs among students has become an alarming phenomenon in various regions, including Medan. This phenomenon can lead to criminal acts, violence, and other deviant behaviors that disrupt public order and jeopardize the students' future. Schools, as educational institutions, play a significant role in preventing the formation of motorcycle gangs among students. This research aims to identify and analyze the role schools play in preventing the formation of motorcycle gangs among students, with a case study at SMK Bina Taruna 1 Medan. The methodology used in this study is a qualitative approach with a case study method. Data were obtained through in-depth interviews with teachers, school principals, and students, as well as observations of the policies and programs implemented by the school concerning the prevention of motorcycle gangs. Additionally, secondary data such as school documents and police reports were analyzed to support the research findings. The research results show that SMK Bina Taruna 1 Medan has undertaken various preventive efforts to prevent the formation of motorcycle gangs among students. These include character development programs, positive extracurricular activities, strict supervision of student behavior, and collaboration with the police and parents. The conclusion of this study is that schools have an important role in preventing the formation of motorcycle gangs through educational approaches, supervision, and partnerships with relevant stakeholders. However, more integrated and sustainable efforts are still needed to ensure more effective and long-term results.